The Impact of Person-Organization Fit on the Corporate Brand Perception of Employees and Customers - Yaniv, Eitan; Farkas, Ferenc (Marketing & Menedzsment, 2019)
One of the major problems companies face in the marketplace is a gap existing between the corporate brand values as perceived by the customers and the corporate brand values which were declared as such by the management. It is shown here that Person-Organization Fit (POF) - i.e. the fit between organizational values and the individual values of the employees - can play a significant role in closing that gap. In this research the impact of POF has been viewed from an external perspective. Conclusions derived from the research are that employees’ POF positively affects the extent to which they perceive their corporate brand values as congruent with those which were declared by the management and that this brand perception level of employees positively affects the perception level of the customers. A high perception level of customers means a higher trust in the brand and in the corporate which stands behind it, and the result is a more powerful brand.